Hydrodynamic phenomena that occur during the movement of passenger ships in the canal - Škiljaica Ivan V.; Škiljaica Vladimir S.; Živković Mirjana I. (Tehnika, 2025)
It is known that the navigable part of the canal network of the Danube-Tisza-Danube system was built, restored and reconstructed in total length of almost 600 kilometers, while it was designed and grouped into three classes according to the size of the relevant vessel. Water levels in the canal system are kept within the required limits, thus ensuring nominal navigational characteristics. During the exploitation so far, the channels of this system have been mostly used by ships for the transport of various types of cargo. In recent years, the idea of introducing passenger ships on certain lines, as well as the introduction of ships for the transport of tourists along the attractive routes of this system, has been proposed. Until today, this method of navigation has not been used, appart for sporadically smaller vessels and boats. The first, and so far the only, research into the navigation of passenger ships in the canals was carried out in 1968 by the Laboratory for Examining Ships and Waterways of the Faculty of Transportation from Belgrade. The aim of this research was, among other things, to establish the basis for the proper use of vessels, as well as the planning and organization of canal transportation. In addition, the conducted research had the task of collecting data needed for the design of canal passenger ships. In the paper, the authors performed a comparative analysis of the measured and observed hydrodynamic phenomena that occurred during the experiment carried out with the "Hydrobus" type passenger ship during its navigation in one of the canals of the Danube-Tisza-Danube system and the same parameters calculated using appropriate calculation methods.